Overcoming Managerialism Power, Authority and Rhetoric at Work - Spillane, Robert, 1945- (De Gruyter, 2022)
Managerialism has often been defined as an ideology, according to which the effective and efficient running of commercial firms, not-for-profit organizations and public administrations is delivered by individuals who possess superior formal knowledge and expertise in management. Arguing to their exclusive education, managers deprive employers and employees of decision-making power and ensconce themselves systematically in the power structure of workplaces to advance their own interests and agenda. The central thesis of Overcoming Managerialism is that resisting and overcoming managerialism necessitates the re-establishing of the conceptual distinction between power and authority. Second, it requires the rehabilitating of authoritative management as a protection against authoritarian practices. Authority, properly conceived, redirects power to technical experts and professionals and thereby limits managerial power. The authors discuss ten contentions which, taken together, represent a theory of the foundation of management in which authority, power and rhetoric are central concepts. This book combines academic scholarship with a readable critique of managerialism. It will be of interest to both management scholars and students.